Implementation of the Stunting Prevention Program by the Office of Population Control and Family Planning of Mesuji Regency - Mila Dahliana Harahap; Ambya; Arif Darmawan (International Journal of Economics, Business and Innovation Research, 2025)
Stunting is a chronic nutritional problem that has a serious impact on the quality of human resources (HR) and long-term economic growth. Mesuji Regency is one of the areas with a relatively high stunting prevalence rate in Lampung Province. This study aims to analyze the role of the Office of Population Control and Family Planning (PPKB) in the implementation of stunting prevention policies in Mesuji Regency, evaluate its implementation, and identify program success indicators. The research method used is qualitative with a policy evaluation approach using the CIPP model (Context, Input, Process, Product). The results show that the PPKB Office has a strategic role as a cross-sector coordinator in the Stunting Reduction Acceleration Team (TPPS), an implementer of educational programs such as Bina Keluarga Balita (BKB), and regional innovations such as the Community Movement Against Stunting (GEBERMAS). Evaluation of the implementation indicated good achievements in the context and input aspects, marked by regulatory support, leadership commitment, and adequate budget allocation. However, challenges remain, including limited human resources, unequal basic facilities, and suboptimal coordination among government agencies. The decrease in the number of stunted children from 1,456 in 2022 to 1,083 in 2023 demonstrates the positive impact of the implemented policies. Strengthening cross-sector coordination, improving the availability of supporting facilities, and increasing community participation and awareness are essential to ensure the sustainability of stunting prevention programs.